The role of difficulty in emotion regulation and body image disorder in prediction unhealthy eating behavior and attitude in adolescent girls - Vafapor, Hosna; Karami, Jahangir; Momeni, Khodamorad (Researcher Bulletin of Medical Sciences, 2022)
Objective: One of the most important traumatic problems among adolescent girls is unhealthy eating behaviors and attitudes among them, which can increase stress in normal relationships and also damage their physical and mental health. Therefore, the present study aims to determine the role of difficulty in emotion regulation and body image disorder in prediction unhealthy eating behaviors and attitudes in adolescent girls in Kermanshah. Materials and Methods: The method of the present study was descriptive of correlation type and the statistical population included all adolescent girls in Kermanshah in 2019. By available sampling method and based on Morgan table, 350 people were selected as a sample. Research instruments included the Unhealthy Eating Behaviors and Attitudes Scale, the Grater and Roemer emotion regulation scale, and the Lillton body image anxiety questionnaire, all three of which were valid and reliable. To analyze the data, Pearson correlation and stepwise regression analysis were used simultaneously, which the data were finally analyzed by SPSS-22 software. Results: the components of difficulty in emotion regulation and body image disorder have a significant effect on unhealthy eating behaviors and attitudes. The predictor variables of both can accurately explain 9% of unhealthy eating behaviors and attitudes. Conclusion: The results showed that unhealthy eating behaviors and attitudes in adolescent girls could be a challenge in the mental and physical health of this group. Therefore, it is suggested that health counselors and therapists pay attention to this important issue.